Kinerja Guru Kelas Dalam Menyusun dan Mengembangkan Perangkat Pembelajaran di SD Negeri KIP Maccini Makassar - Nurul Hikmah; Syarifuddin Cn Sida; Idawat Idawat (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
Abstract;                      Nurul Hikmah, (2019). Teacher performance class in organizing and developing learning devices in the state SDN KIP Maccini Makassar. Guided By Syarifuddin Cn Sida and Idawati.This study aims to study the performance of the teachers in developing and expanding learning devices in the state SDN KIP Maccini Makassar. This type of research uses qualitative descriptive research methods. The location in this research is the state elementary school KIP Maccini Makassar. The types of data in this study are primary data obtained directly from the informant and secondary data in the form of documents relating to the issues and the research reports. The instruments in this research are own researchers and supporting data collection tools are interview guidelines. Based on the results of the study that the performance of teachers certified by SDN KIP MACCINI in the planning of learning received an average score of 18.32 in the category quite effective. The assessment showed that teachers certified by SDN KIP MACCINI were well-performing in the planning of learning. Keywords: teacher performance; Learning devices